Fleshly love, platonic love in the Symposium - Fierro, María Angélica (Estudios de Filosofía, 2019)
Here I aim to show how the views on the body in Plato´’s Symposium must be considered not as contradictory but as complementary. The three main thesis of this paper are: a) The body is essential for the triggering of “erôs”, insofar as sexual attraction to beautiful bodies is the most natural way in which anyone can start to develop an erotic experience. b) The ascent towards beauty itself implies detachment from a particular body as such in order to move to an appraisal of it from a wider, more general understanding. c) Additionally the loving relationship between Socrates and beautiful young men shows that the physical dimension of “erôs” is never completely eradicated by Plato but, on the contrary, it works as an essential trigger of desire.